Metabolism, excretion, and therapeutic window - Allegaert, Karel (Henry Stewart Talks, 2024)
Metabolism, Excretion, Therapeutic window, Clearance, Phase I and phase II metabolic enzymes, Covariates of activity & personalized medicine, Renal excretion